Literary Language and Cognitive Experience: How the Reading of English Literary Fiction Shapes Empathy, Theory of Mind, and Social Cognition - Dr. Chander Mohan (Journal of International Islamic Law, Human Right and Public Policy, 2026)
This paper explores the intersection of literary language, cognition, and social understanding, examining the empirical evidence for the hypothesis that sustained engagement with English literary fiction cultivates empathy, enhances Theory of Mind (ToM) capacities, and reshapes social cognition more broadly. Synthesising findings from cognitive poetics, developmental psychology, and experimental aesthetics, the paper argues that the particular textual features of literary fiction including deep point-of-view narration, affective free indirect discourse, moral ambiguity, and defamiliarisation create distinctive cognitive demands that exercise and refine the mental capacities underlying interpersonal understanding. The paper also addresses methodological objections to this claim, considers the role of genre and text difficulty, and discusses implications for reading pedagogy and the place of literary education in cognitive and social development.